Assisting the visually impaired people using image processing - Rahman, Ferdousi; Ritun, Israt Jahan; Farhin, Nafisa (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.